2014
DOI: 10.1186/s12931-014-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal exposure of maternal secondhand smoke (SHS) increases fetal lung expression of RAGE and induces RAGE-mediated pulmonary inflammation

Abstract: BackgroundReceptors for advanced glycation end-products (RAGE) are immunoglobulin-like pattern recognition receptors abundantly localized to lung epithelium. Our research demonstrated that primary tobacco smoke exposure increases RAGE expression and that RAGE partly mediates pro-inflammatory signaling during exposure. However, the degree to which RAGE influences developing lungs when gestating mice are exposed to secondhand smoke (SHS) has not been determined to date.MethodsTimed pregnant RAGE null and wild ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…An underlying mechanistic theme of the smoke-related disease states outlined in this review is chronic inflammation, in which RAGE is a key modulator. Essential to understanding the clear link between RAGE and disease progression is the key concept that RAGE expression is increased by exposure to tobacco smoke [5,209,210,211,212] and the induction of RAGE causes inflammatory disease symptoms similar or identical to the ones described herein [23,195,213,214,215,216,217]. …”
Section: Rage: a Plausible Unifying Mechanismmentioning
confidence: 94%
“…An underlying mechanistic theme of the smoke-related disease states outlined in this review is chronic inflammation, in which RAGE is a key modulator. Essential to understanding the clear link between RAGE and disease progression is the key concept that RAGE expression is increased by exposure to tobacco smoke [5,209,210,211,212] and the induction of RAGE causes inflammatory disease symptoms similar or identical to the ones described herein [23,195,213,214,215,216,217]. …”
Section: Rage: a Plausible Unifying Mechanismmentioning
confidence: 94%
“…Immunoblotting was performed as previously outlined by our laboratory [43]. Briefly, tissues were homogenized in protein lysis buffer (RIPA, Fisher Scientific, Pittsburg, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, studies have reported that exposure to cigarette's smoke and its toxins could lead to mutation in gamete and embryo [11]. Also increased chance of abortion in the first trimester [12], preterm delivery [13], low birth weight [14,15] and development problems is respiratory system of the embryo [16] have been reported after exposure to cigarette's smoke. Therefore it is necessary to give priority to programs for reduction of exposure of pregnant women to cigarette's smoke among pregnancy care programs.…”
Section: Introductionmentioning
confidence: 99%